Burns within the South African context - Motsepe, Tshepang Arthur (International Surgery Journal, 2025)
Burn injuries are a major cause of morbidity and mortality worldwide, with significant physical and psychological sequelae. The application of trauma resuscitation principles can substantially reduce the impact of these injuries. In South Africa, their incidence is closely linked to socioeconomic factors and their management requires a coordinated multidisciplinary approach.